Tremors in Children - Sharma, Nutan (Seminars in Neurology, 2026)
Tremor is a hyperkinetic movement disorder that consists of rhythmic, involuntary oscillatory movement of a body part. It may be present at birth or develop later during childhood. Pediatric tremor may be an isolated disorder or a sign of an underlying genetic and/or neurologic disease. This review provides a summary of the features and classification of pediatric tremors, recommended clinical evaluation, and currently available treatments.
Keywords: pediatric tremors; hyperkinetic movements; ET